Temporal variation of vitellogenin synthesis in Ectatomma tuberculatum (Formicidae: Ectatomminae) workers - Azevedo, Dihego Oliveira; Zanuncio, José Cola; Delabie, Jacques Hubert Charles; Serrão, José Eduardo (Journal of Insect Physiology, 2011)
Workers of the ant species Ectatomma tuberculatum (Ectatomminae) have active ovaries and lay eggs that are eaten by the queen and larvae (trophic eggs). Vitellogenins are the main proteins found in the eggs of insects and are a source of nutrients. The aim of this study was to characterize the period of vitellogenin production in workers of E. tuberculatum. The vitellogenin was identified from queen and worker eggs by SDS-PAGE. Anti-vitellogenin antibodies were obtained and used to detect this protein in the fat body and haemolymph of workers at different ages. Vitellogenin from E. tuberculatum consists of two polypeptides of 31 and 156 kDa. In the eggs of queens, the 156 kDa polypeptide is cleaved into two subunits of 36 and 123 kDa. The analysis of the haemolymph of workers showed that the secretion of vitellogenin varies with age. The secretion is initiated around the fifth day after emergence, with peak production from days 20 to 60, and stops around day 100. The variation in production is related to the different activities performed by the workers within the colony, suggesting that vitellogenin may have an important role in maintaining age polyethism.
Keywords: Vitellogenin; Vitellin; Age polyethism; Trophic egg; Fat body; Ant